The role of the use of combined technologies in the approach to a patient with microstomia - Karina Bittencourt Medeiros; Layla Comel Corso Perito de Bem; Priscila Regina Orso Rebellato; Juliana Merheb Jordão (Sociedade Brasileira de Dermatologia (SBD), 2020)
Facial surgeries are often challenging for surgeons due to their complex anatomy, aesthetic and functional importance. Interventions in the cosmetic subunit that comprises the eyebrows can be particularly difficult. This case report aims to demonstrate the use of island flap in this region. We performed the excision of melanocytic nevus, with a good outcome and absence of postoperative complications. This technique is commonly used for facial reconstruction; however, the literature describes only a few cases using this method for eyebrow reconstruction.